Salinity effect on the vegetative growth of Andean blackberry plants (Rubus glaucus Benth.) inoculated and non-inoculated with mycorrhizal fungi - Cardona, William Andrés; Gutiérrez D., Joan Sebastián; Monsalve C., Oscar Iván; Bonilla C., Carmen Rosa (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Andean blackberry is usually sown in soils without salinity limitations, but the use of fertilizers based on sources of chemical synthesis that do not take  into account nutritional requirement or the use of chicken manure without composting  can cause a long-term salinity effects. In this research, the effect of different concentrations of a saline solution (0, 40, 80 and 120 mM NaCl) on the vegetative growth and nutrient uptake of Andean blackberry plants (Rubus glaucus Benth.), inoculated and non-inoculated with mycorrhizal fungi (Glomus proliferum Dalpe & Declerck strain GB02), was evaluated. A completely randomized design with a factorial arrangement (4×2) was established. Radical growth, accumulation of fresh and dry matter, concentration and absorption of nutrients in the leaves, stems and roots were evaluated. It was found that inoculation with mycorrhizal fungi increased plant growth under saline stress (40 and 80 mM) because of a possible increase in the acquisition of mineral nutrients with low mobility and a reduced intake of Na. At 120 mM, the Ca uptake decreased and Na increased, resulting in a lower water consumption. The plants diminished the capacity to produce enough photo-assimilates to promote development of the plants and the mycorrhizal fungi; therefore, growth and biomass production decreased. The association with the fungus allowed for a greater selectivity by the plants for the potassium ion than the sodium ion.